Gradient Projection Method for Simulation-Based Dynamic Traffic Assignment - Yang, Inchul; Jayakrishnan, R. (Transportation research record, 2012)
A gradient projection method is presented to solve the problem with dynamic traffic assignment. The gradient projection scheme is a feasible direction algorithm that operates directly in the space of path flows. The algorithm was applied to a simulation-based model for dynamic traffic assignment that used microscopic simulation for supply-side modeling. The formulation used link cost functions that were separate for moving and queuing vehicles on each link, so that the formulation could effectively capture the effects of traffic dynamic characteristics on each group, especially in arterial networks. The model and solution algorithm were applied to a small real-world network, and the performance was studied. The gradient projection algorithm avoided the problem of convergence to nonoptimal conditions shown by the prevalent method of successive averages and demonstrated significantly faster convergence.